Cognitive Load and AI-Assisted Learning in Thai Higher Education: A Structural Model Approach - Rungchatchadaporn Vehachart; Ratna Yunita Setiyani Subardjo (The Indonesian Institute of Science and Technology Research, 2026)
The integration of artificial intelligence (AI) in higher education has significantly transformed teaching and learning processes. While AI-assisted learning tools offer personalized feedback and adaptive learning environments, their cognitive implications remain underexplored, particularly in non-Western contexts. This study investigates the impact of AI-assisted learning on cognitive load and learning outcomes in Thai higher education. Using Cognitive Load Theory (CLT) as a framework, a quantitative approach with PLS-SEM was applied to data from 312 students. The findings indicate that AI-assisted learning reduces extraneous cognitive load while enhancing germane cognitive load. Student engagement mediates the relationship between cognitive load and learning outcomes, while cultural factors moderate AI usage effects.